Teaching Routines in German Geography Classrooms: A Case Study in North Rhein-Westphalian Gymnasiums - Krohmer, Maxim; Budke, Alexandra (Advances in Social Sciences Research Journal, 2021)
Teachers develop their professional competence throughout their careers through education, experience, and reflection. To achieve this, routines are a vital factor, which can be described by short sequences of teacher actions with specific functions within a lesson. These short sequences of teacher behavior within a lesson can be observed particularly well in German geography classes, because already during the academic education and the subsequent traineeship a specific lesson sequence, consisting of three phases, is taught to the prospective teachers. This article focuses on the question of what routine in everyday teaching by geography teachers looks like with the aim of contributing to the understanding of professional teaching in geography education. To achieve this, 112 geography lessons of 45 minutes and 38 teachers were observed in German Gymnasiums in North Rhine-Westphalia via observation sheets. Subsequently, the collected data was analyzed by frequency analysis. The results show that the observed teachers have patterns of routine within specific phases in class, such as in the use of teaching methods, material and media, and classroom management.